The First World War and the nationality question in Europe : global impact and local dynamics - Núñez Seixas, Xosé M., 1966- 1966- Herausgeber; The International Context of the Galician Language Brotherhoods and the Nationality Question in Interwar Europe (Veranstaltung : 2016 : Santiago de Compostela) (National cultivation of culture, 2021)
"This volume assembles the papers presented at the conference The International Context of the Galician Language Brotherhoods and the Nationality Question in Interwar Europe (Council of Galician Culture, Santiago de Compostela, October 2016). The different contributions, written by historians, political scientists and linguists, shed new light on the political development of the nationality question in Europe during the First World War and its aftermath, covering theoretical developments and debates, social mobilization and cultural perspectives. They also address the topic from different scales, blending the global and transnational outlook with the view from below, from the local contexts, with particular attention to peripheral areas, whilst East European and West European nationalities are dealt with on an equal footing, covering from Iberian Galicia to the Caucasus. Contributors are: Bence Bari, Stefan Berger, Miguel Cabo, Stefan Dyroff, Lourenzo Fernández Prieto, Johannes Kabatek, Joep Leerssen, Ramón Máiz, Xosé M. Núñez Seixas, Malte Rolf, Ramón Villares, and Francesca Zantedeschi."